Soft Elastomeric Nanopillar Stamps for Enhancing Absorption in Organic Thin‐Film Solar Cells. Issue 3 (9th October 2012) - Hyun, Jerome K.; Ahn, Changui; Kang, Hyunbum; Kim, Hyeong Jun; Park, Junyong; Kim, Ki‐Hyun; Ahn, Chi Won; Kim, Bumjoon J.; Jeon, Seokwoo
<x xml:space="preserve">Abstract</x> An elastomeric poly(dimethylsiloxane) (PDMS) block engraved with periodically arrayed nanopillars serves as a transferable light‐trapping stamp for encapsulated organic thin‐film solar cells. Diffracted light rays from the stamp interfere with one another and self‐focus onto the active layer of the solar cell, generating enhanced absorption, as indicated in the current density–voltage measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>